PENGARUH PEMBELAJARAN KOOPERATIF DENGAN BANTUAN LABORATORIUM MINI MELALUI PENDEKATAN TEORI BRUNER TERHADAP HASIL BELAJAR MATEMATIKA SISWA SEKOLAH DASAR 013 TAMPAN PEKANBARU - Anggraini, Rini Dian (Jurnal Pilar Sains, 2008)
The low of achievement students in learning mathematics is still a problem which has not been solvedyet. This is because of various factors like the designed of learning strategies. The teachers do notconsider the stages of students’ mental development and neither facilitate with the optimal learningfacilities. Beside the school facilities have not been sufficient for teaching geometry. These factors arecauses that materials delivery is not appropriate with students’ ability; therefore, we should do effortfor the improvement. This research is the implementation of cooperative learning with the aid the minilaboratory through Bruner’s theory. The aim of this research is to know the influence of cooperativelearning with the aid of mini laboratory through Bruner’s theory which is related with the entry abilityof the students. This research was conducted at the second semester of the 3rd of SD 013 TampanPekanbaru in academic year 2007/2008. The research design is treatment by block design (2x2), andthe sampel is 77 pupils. The data was gain from the result of learning which had been tried out forvalidity and reliability. The result of the data analysis indicates: (1) The cooperative learning methodwith the aid of mini laboratory through Bruner’s theory is more effective to increase the students’achievement in mathematics than the conventional leaning model;(2) The cooperative learning methodwith the aid of mini laboratory through Bruner’s theory is more effective to increase the studentsachievement in mathematics with high entry ability than the conventional learning model; (3) Thecooperative learning method with the aid of mini laboratory through Bruner’s theory is more effectiveto increase the students achievement in mathematics with low entry ability than the conventionallearning model; (4) There is no significant interaction between learning method and the level ofstudents’ ability to the result of learning. The result of this research indicate that there is an influencein using the cooperative learning method with the aid of the mini laboratory through Bruner’s theoryon student achievement in mathematics with different level of student entry ability.Keyword: Cooperative Learning, Mini Laboratory, Bruner’s theory